Respuesta :

The first term is,  x2  its coefficient is  1 .
The middle term is,  -3x  its coefficient is  -3 .
The last term, "the constant", is  -70 

Step-1 : Multiply the coefficient of the first term by the constant   1 • -70 = -70 

Step-2 : Find two factors of  -70  whose sum equals the coefficient of the middle term, which is   -3 .

     -70   +   1   =   -69     -35   +   2   =   -33     -14   +   5   =   -9     -10   +   7   =   -3   That's it


Step-3 : Rewrite the polynomial splitting the middle term using the two factors found in step 2 above,  -10  and  7 
                     x2 - 10x + 7x - 70

Step-4 : Add up the first 2 terms, pulling out like factors :
                    x • (x-10)
              Add up the last 2 terms, pulling out common factors :
                    7 • (x-10)
Step-5 : Add up the four terms of step 4 :
                    (x+7)  •  (x-10)

x-10=0          x+7=0
 +10 +10          -7 -7
    x=10             x=-7
ACCESS MORE